Seroprevalence of IgM/IgG and Neutralizing Antibodies against SARS-CoV-2 in Unvaccinated Young Adults from Mexico Who Reported Not Having Had a Previous COVID-19 Infection - Diana Lourdes Padilla-Bórquez; Mónica Guadalupe Matuz-Flores; Jorge Hernández-Bello; Gabriela Athziri Sánchez-Zuno; Samuel García-Arellano; Edith Oregon-Romero; Melva Guadalupe Herrera-Godina; Guillermo González-Estevez; Norma Patricia Adan-Bante; Jesús Alfredo Rosas-Rodríguez; José Francisco Muñoz-Valle (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus that causes coronavirus disease 2019 (COVID-19). It is estimated that more than half of new infections are transmitted by asymptomatic people; therefore, the isolation of symptomatic people is not enough to control the spread of the disease. Methods. A total of 171 unvaccinated young adults (18–35 years) from Sonora, Mexico, who underwent a structured survey to identify prior COVID-19 infections, were included in this study. A qualitative determination of anti-SARS-CoV-2 antibodies in serum was performed by lateral flow immunoassay (Certum IgG/IgM Rapid Test™ cassette kit) and neutralizing antibodies were also determined (GenScript cPass assay). Results. A total of 36 people reported a history of COVID-19 infection, and 135 reported no history of COVID-19. In contrast, 49.6% (67/135) of individuals who had not reported a previous SARS-CoV-2 infection were seropositive to the rapid anti-SARS-CoV-2 antibody test, and 48.1% (65/135) of them had neutralizing antibodies. Conclusions. These results suggest that in young adults, SARS-CoV-2 infections could be asymptomatic in a high percentage of individuals, which could contribute in part to the slow control of the current pandemic due to the large number of asymptomatic cases that are contagious and that could be a silent spread of the virus.